Internal Control Unit Strategy in Implementing Internal Control - Dwi Sukesi, Udhin; Hadiyati, Ernani; Muawanah, Umi (International Journal Labs, 2024)
This study aims to describe the implementation of the Government Internal Control System (SPIP) at Dr. Radjiman Wediodiningrat Mental Hospital, Lawang, Malang and to develop a strategic plan from the Internal Audit Unit (SPI) in conducting supervision of the Mental Hospital. This research is qualitative research. The informants are the Head of SPI and other respondents. In formulating alternative strategies, SWOT analysis is used with the IFAS and EFAS approach methods. The results showed that SPI is in quadrant I (supporting growth strategy), which has strong internal strengths to grow in seizing existing opportunities. The resulting strategy is to improve internal control in the RSJ through the formation of the SPIP Task Force in organizing internal control in the hospital, increasing the knowledge and understanding of the heads of work units, on all matters relating to inherent supervision within the scope of their work units and utilizing information technology by creating a Supervisory Information System application to support supervisory performance, especially in terms of organizing SPIP in the hospital. The implications of this research are significant for enhancing internal control systems and strategic planning within healthcare institutions. By identifying SPI's current position and proposing targeted strategies, this study provides actionable recommendations for improving internal oversight and control mechanisms. The formation of a dedicated SPIP Task Force and the development of a Supervisory Information System application are expected to strengthen internal controls, streamline supervision processes, and enhance overall organizational efficiency.